2021
DOI: 10.1186/s43093-021-00057-w
|View full text |Cite
|
Sign up to set email alerts
|

Multi-grade fuzzy assessment framework for software professionals in work-from-home mode during and post-COVID-19 era

Abstract: The pandemic novel Coronavirus disease and the resulting lockdowns have contributed to major economic disturbances around the world, forcing organisations to extend the work-from-home (WFH) option to their employees wherever feasible. The current major challenge of this option is maintaining the efficiency and productivity of the employees across the organisations. It is therefore important to understand the impact of this make-shift arrangement of WFH policy and their underlying effects that may affect the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…Las estrategias con mayor aceptación fueron la implementación de un programa de reducción de estrés laboral y el desarrollo de un programa de compensación no económica, apoyando lo manifestado por Rahm et al (como se citó en Moscoso y Salgado, 2021), Lorenzo y Díaz (como se citó en Herrera y Antúnez, 2021), Raza et al (2017) y Salvador et al (2021. Esta situación congrue con los problemas que ha potenciado la COVID-19 ligados a la generación de estrés, traumas y otras patologías emocionales que se originan por el cambio drástico de la forma de trabajo y el propio contexto de la pandemia (Abdelghani et al, 2020;Kumar et al, 2021;Martí et al, 2021;Suresh y Gopakumar, 2021;Thron et al, 2021).…”
Section: Discussionunclassified
“…Las estrategias con mayor aceptación fueron la implementación de un programa de reducción de estrés laboral y el desarrollo de un programa de compensación no económica, apoyando lo manifestado por Rahm et al (como se citó en Moscoso y Salgado, 2021), Lorenzo y Díaz (como se citó en Herrera y Antúnez, 2021), Raza et al (2017) y Salvador et al (2021. Esta situación congrue con los problemas que ha potenciado la COVID-19 ligados a la generación de estrés, traumas y otras patologías emocionales que se originan por el cambio drástico de la forma de trabajo y el propio contexto de la pandemia (Abdelghani et al, 2020;Kumar et al, 2021;Martí et al, 2021;Suresh y Gopakumar, 2021;Thron et al, 2021).…”
Section: Discussionunclassified
“…This paper develops Covid-19 preventive and safety measures assessment framework using multi-grade fuzzy. This methodology is well known and simple to compute index value, and it's extensively applied in the service sector ( Suresh and Gopakumar, 2021 ; Ranjitha et al, 2022 ). Multi Grade Fuzzy approach has been increasingly popular in the field of operations management ( Subramanian and Suresh, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…The study also found that having the appropriate tools or technologies at home boosted workers' productivity. Suresh & Gopakumar [90] conducted research on how the IT sector transitioned to telework without sacrificing productivity or efficiency in support of that. They concluded that offering the right chances for training and development not only increased productivity but also fostered both personal and professional development.…”
Section: Telework and Productivitymentioning
confidence: 99%